Practical application of precision oncology in adult onset craniopharyngiomas - Biswas, Chandrima; Mansur, Guilherme; Wu, Kyle C.; Prevedello, Daniel M.; Ghalib, Luma (Frontiers in Endocrinology, 2024)
Introduction: Craniopharyngiomas (CPs) are benign and rare tumors found in adults. Their location close to vital neurovascular structures makes traditional treatment modalities (surgery and radiation) challenging and potentially fraught with morbidity. The 2021 WHO classification has divided what was previously considered two subtypes of craniopharyngioma into separate entities. Identification of specific molecular driver mutations in each type-BRAF V600E in papillary craniopharyngiomas (PCP) and CTNNB1 in adamantinomatous craniopharyngiomas (ACP) has resulted in a paradigm shift in the management of adult CPs.In this study, we describe our experience in treating PCPs with targeted therapy and highlight nuances in management accounting for current evidence. This review also explores the current scope and application of precision oncology in adult CPs including the experience with ongoing trials and prospects for future research.The high prevalence of targetable mutation in cases of PCP and the efficacy of BRAF inhibitors alone or in combination with MEK inhibitors has improved the disease control in these patients. In the current scenario, while surgery is warranted to obtain histopathological diagnosis, radical resection and its associated risks can be avoided. In case of ACPs, dysregulation of multiple pathways has been implicated. This has prompted the use of a variety of targeted therapies with inconsistent outcomes. The results of ongoing and future trials may define its role in management.